ASSESSMENT OF SHEAR STRENGTH PARAMETERS OF SOIL FROM LOAD MICROPILE TESTS - Karel Vojtasík (Acta Polytechnica CTU Proceedings)
Design and evaluation of the bearing capacity of micropiles are based on shear strength parameters of the soil within which a micropile is installed. These parameters are mostly received from laboratory tests or as an expert evaluation relying on soil description, classification and collected experience. This paper presents an approach that determines cohesion and angle of internal friction from diagrams of displacement on load, these being obtained by compression and traction load tests of real micropiles installed in the known soil. Furthermore, the diagrams are interpreted by the Mohr-Coulomb strength criterion and the desired values of shear strength are thus derived by using it.